THE TITLE KHALÎFAT ALLÂH IN 17TH CENTURY ACEH: Concept and Meanings - Hadi, Amirul (State Islamic University North Sumatra, 2021)
Abstract: This article attempts to study the use of the title ‘khalîfat Allâh’ in seventeenth century Aceh. The main bulk of this inquiry revolves around the concept and meanings of the title, which was adopted from the mainland of Islam. This study is historical in nature and it is done by employing the ‘descriptive analytical’ method. The description of the use of the title khalîfat Allâh and its relations with the Acehnese political structures will be investigated. This step is then followed by the ‘analytical’ part, in which the exploration of the Acehnese conception and the meanings of the title will be given. As a sultanate, Aceh was seen as a khilâfah in its own right in which God’s religion is to be implemented. As Such, the ruler’s task was not only to pursue the prosperity for the country and its people but also to foster God’s religion. Based on this tenet, the head of the state was to hold the title ‘khalîfat Allâh’, which simply meant the ‘deputy of God.’ By this very title a ruler was to possess both political and religious authority. Yet, by holding the religious authority did not necessarily mean that a ruler was a scholar of religion; it can be best described as a ‘religiously sanctioned authority’. Keywords: Aceh, sultanate, khalîfat Allâh, authority, politics, religion